DETERMINAN PENGAMBILAN KEPUTUSAN UNTUK MENIKAH PADA REMAJA DI INDONESIA - Yane Tambing; Mona S Fatiah; Apriyana Irjayanti (JURNAL KESEHATAN REPRODUKSI, 2023)
Abstract Background: Making decisions to marry among teenagers will lead to high rates of child marriage before the age of 18, which will later have long-term risks for the health, psychological, and social problems of teenagers. Objective: Analyzing the determinants that influence the decision to marry among teenagers in Indonesia. Method: This study was cross-sectional by analyzing IDHS data in 2018, where the study sample was 10,619 women aged between 20-24 years who had been married before turning 18 years old. Results: about 72.2% of Indonesian adolescents participated in the decision to get married, another result of the study found that. The factors of sexual experience that were related to education (p-value: 0.001 and AOR:1.94 with 95% CI: 1.52-2.48), information exposure (p-value: 0.002 and AOR: 1.37 with 95% CI: 1.12-1.66) and sexual experiences (p-value=0.001 and AOR=0.64 with 95% CI=0.52-0.79). Education was The dominant variable that influenced the decision-making of marriage in adolescents was education. Conclusion: The decision-making of marriage in adolescents is influenced by education variables, information exposure, and sexual experiences Recommendation: enhancing adolescent participation in PIKRs: promoting healthy marriage and sexuality education through social media. Keywords: determinants, marriage decision-making, Indonesian teenagers.   Abstrak Latar belakang: Memutuskan untuk menikah pada usia remaja dapat berdampak jangka panjang pada pada masalah kesehatan, psikologis dan sosial remaja. Tujuan: Mengetahui deteminan keputusan menikah pada remaja Indonesia. Metode: Penelitian ini berdesain cross sectional dengan menganalisis data SDKI tahun 2018, dimana sampel penelitian sejumlah 10.619 orang wanita berusia antara 20–24 tahun  yang pernah menikah sebelum menginjak 18 tahun. Hasil: Sekitar 72,2% remaja Indonesia berpartisipasi dalam pengambilan keputusan untuk menikah, variabel pendidikan dengan nilai p-value=0,001 serta AOR=1,94 (95% CI=1,52-2,48), keterpaparan media dengan nilai p-value:=0,002 dan AOR=1,37 (95% CI=1,12-1,66) dan pengalaman seks dengan nilai p-value=0,01 dan AOR=0,64 (95% CI:0,52-0,79) berhubungan dengan pengambilan keputusan sendiri untuk menikah pada remaja, dan variabel yang dominan adalah variabel pendidikan. Kesimpulan: Pendidikan, keterpaparan informasi serta pengalaman seks remaja memiliki peran dalam  keputusan menikah. Rekomendasi: Menggalakkan kampanye tentang pernikahan yang sehat serta edukasi seksualitas melalui media sosial serta meningkatkan peran remaja pada Pusat Konseling dan Informasi Remaja (PIKR) yang ada di sekolah.     Kata kunci: determinan, pengambilan keputusan menikah, remaja Indonesia.